2020
DOI: 10.1053/j.ajkd.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

We Can Finally Stop Worrying About SGLT2 Inhibitors and Acute Kidney Injury

Abstract: S odium glucose transporter 2 (SGLT2) inhibitors, originally approved solely as antihyperglycemic agents for the treatment of type 2 diabetes mellitus (T2DM), are increasingly recognized for their distinctive kidney and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Despite no significant changes, the daily percentage change from baseline (geometric mean: 1. 35 3/Figure 1).…”
Section: Effect Of Dapagliflozin On Uacr and Egfrmentioning
confidence: 99%
“…Despite no significant changes, the daily percentage change from baseline (geometric mean: 1. 35 3/Figure 1).…”
Section: Effect Of Dapagliflozin On Uacr and Egfrmentioning
confidence: 99%
“…The trials have not reported of an excess hazard of AKI with SGLT2 inhibitors in subtypes of studied patient at particular risk of volume contraction (including individuals with HFrEF and CKD in EMPEROR‐Reduced, among whom ∼90% were on RAS blockade and diuretics, and two‐thirds also treated with an MRA 32 ). One potential protective mechanism of SGLT2 inhibition may be reduced risk of ischaemic‐reperfusion injury or renal tubular hypoxia from the lowered metabolic demand from inhibited sodium–glucose co‐transport 71 . Conceivably, a reduction in AKI risk may also translate into benefits on CKD progression, providing a mechanistic explanation for beneficial effect of SGLT2 inhibition on eGFR slopes in individuals with heart failure 19,32,33,72 …”
Section: Effects On Kidney Diseasementioning
confidence: 99%
“…23 While the mechanisms responsible for reducing AKI risk with SGLT2 inhibitors are not known, several possibilities exist. 8 Firstly, SGLT2 inhibitors reduce tubular ischemia by attenuating energy-intensive solute reabsorption, akin to how beta-blockers are used to reduce myocardial ischemia by reducing cardiac workload. 24 Secondly, SGLT2 inhibition is associated J o u r n a l P r e -p r o o f with a rise in hematocrit, thereby increasing oxygen carrying capacity and kidney oxygenation, thereby reducing ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subsequent work has identified biologicallyplausible mechanisms whereby SGLT2 inhibition could reduce AKI risk. 7,8 Understanding the relation between SGLT2 inhibition and risk of AKI in patients with CKD and albuminuria is relevant since patients with CKD experience higher rates of AKI than patients with normal or near normal kidney function. The Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease (DAPA-CKD) trial demonstrated that the SGLT2 inhibitor, dapagliflozin, reduced the risk of kidney failure and heart failure hospitalization, and prolonged survival in patients with CKD with and without type 2 diabetes.…”
Section: • Saes Of Acute Kidney Injury Occurred Less Frequently With Dapagliflozin Versus Placebo Introductionmentioning
confidence: 99%